Housing Price Bubble Explosion: Evaluation of the Problem - Belinskaja, Larisa; Rutkauskas, Virgilijus (Ekonomika, 2007)
The problem of real estate price bubble is analysed in relation to the development and growth of the economy of Lithuania. By evaluating theoretical and practical-historical aspects of formation of the housing prices’ bubble, as well as the opinion of renown experts of the country, the formation of the present situation is substantiated by specifying economic and psychological reasons (it is accentuated that these factors tendentiously influence the market of real estate in Lithuania). More than once the historical guidelines of many countries had disclosed the threat of real estate prices’ fluctuation to the harmonious development of a national economy. In 2003, when Lithuania became one of the most rapidly developing economies, began an unprecedented growth of housing prices. Encouragements of experts to resist euphoria came short of living standards’ growth and the psychological impulse that followed the tendency of price growth. Hence it became possible to state that the real estate price bubble was taking shape and might threaten the national economy. The perception of external signs, with reference to assumptions of economic growth and the interpretation of different factors’ interface, enabled to display the influence of the real estate market on the economy and welfare of the country. The estimation of economics growth, which in this article is based on fundamental factors and psychological motives, has displayed the complicated and often difficult to forecast influence of real estate market development on vital processes in economics. By generating insights and future prospects, a possible scenario of factors’ development is given in association with presumptive dates of the national currency replacement with Euro. This event is one of the most important economic factors that have laid foundations for causeless psychological motives in the real estate market. When in 2006 Lithuania didn’t accomplish the requirements of convergence and therefore couldn’t replace its currency with the common currency of European Union, Euro, the growth of real estate prices got slower and influenced the psychological motives of potential customers in the context of the new currency. It is very likely that years 2010-2012 (the presumptive time when the national currency might be replaced with Euro) will enable the participants of the market to come to more rational decisions with reference to the recent past; however, it might be impossible to avoid short-term fluctuations that might be not so threatful. However, when the foundations are rocked, some part of shivers will be absorbed by the insurance sector which will level the negative consequences for people, business and the country. as well as prevent from destroying the productive results of the rapid development.